HUBUNGAN PENGETAHUAN, SARANA PRASARANA DAN PERAN GURU TERHADAP PHBS PADA SISWA SMPIT AL-FITYAN KUBU RAYA KALIMANTAN BARAT - Handayani, Lina; Khalidah, Karimatul (VISIKES, 2025)
Background: The proportion of PHBS (Clean and Healthy Living Behavior) implementation in West Kalimantan, particularly in Kubu Raya Regency, remains relatively low, reaching only 43% in 2021. Factors contributing to the lack of PHBS implementation include predisposing factors, enabling factors, and reinforcing factors. The inadequate application of PHBS can lead to diseases, one of which is hepatitis A. In 2023, an outbreak of hepatitis A occurred in a boarding school in Kubu Raya Regency, namely SMPIT Al-Fityan Kubu Raya, with a total of 136 affected students. This study aims to determine the relationship between knowledge, facilities and infrastructure, and the role of teachers with clean and healthy living behavior among students at SMPIT Al-Fityan Kubu Raya, West Kalimantan. Methods: This study used a Cross-Sectional research design with Chi-Square analysis. The sample of this study amounted to 148 people with purposive sampling techique. The instruments used were questionnaires and observation sheets. Results: The results show that students at SMPIT Al-Fityan Kubu Raya have a good level of knowledge (68.9%), good facilities and infrastructure (62.2%), a good role of teachers (60.1%), and a good level of PHBS (Clean and Healthy Living Behavior) (70.9%). There is a relationship between knowledge (p=0.005; OR=3.055), facilities and infrastructure (p=0.007; OR=2.882), and the role of teachers (p=0.000; OR=6.048) with clean and healthy living behavior among students at SMPIT Al-Fityan Kubu Raya, West Kalimantan. Conclusion: There is a relationship between knowledge, infrastructure and the role of teachers towards clean and healthy living behavior with clean and healthy living behavior in students of SMPIT Al-Fityan Kubu Raya West Kalimantan.